If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 1 = y + 10 Reorder the terms: 1 + 2y = y + 10 Reorder the terms: 1 + 2y = 10 + y Solving 1 + 2y = 10 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 1 + 2y + -1y = 10 + y + -1y Combine like terms: 2y + -1y = 1y 1 + 1y = 10 + y + -1y Combine like terms: y + -1y = 0 1 + 1y = 10 + 0 1 + 1y = 10 Add '-1' to each side of the equation. 1 + -1 + 1y = 10 + -1 Combine like terms: 1 + -1 = 0 0 + 1y = 10 + -1 1y = 10 + -1 Combine like terms: 10 + -1 = 9 1y = 9 Divide each side by '1'. y = 9 Simplifying y = 9
| -x-5y=-28 | | 6(x-2)+1=3x+3(-2+x) | | T=2pirh+2pir^2 | | f(-2)=1/2x-4 | | 80=36x+2 | | (17*x)/36=102/36 | | (x=2)/3-x/6=5/3 | | =8sinx*8sinx | | 17x/36=102/36 | | 2sin=-1.4 | | Y=(-4/3)×-5 | | 14*350=x | | 12x-18=8x+22 | | 6(2x-10)+22=3x+16 | | 527+159=x | | r=2742-127 | | 12=15(z−1/5) | | 9r+8=0 | | 12=15(z−1/5) | | 9r+88=0 | | 4/3x6^3 | | x-0.2x=100 | | 0.8x=100 | | 298.3*44.6= | | -4w+2=10 | | 3m^3-6m^2n-24n^2m=0 | | 4/5-2/3=x/9 | | 12-8x+4=0 | | t=18-9 | | 0.56=0.04-1.9 | | 18n^2+12n=0 | | 24n^2-19n+2=0 |